2010
DOI: 10.1177/0731684409358470
|View full text |Cite
|
Sign up to set email alerts
|

Physico-mechanical Effects of Surface-modified Sorgum Stalk Powder on Reinforced Rubber

Abstract: Stalk of sorghum was crushed into fine particle size and given three surface treatments: with groundnut oil, alkali, and 3-chloro-2-hydroxyl propyl trimethylammonium chloride. It was presumed that the oil treatment will preclude any negative surface potential that cellulose is known to acquire in aqueous environment. The alkali treatment was to remove the natural surface admixtures but to preserve the negative surface potential, and the tertiary ammonium salt was to confer positive potential to it. The four sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…1 shows the tensile strength continuously decreases with the increasing percentage of RS. Similar result was found by Yakaba et al [8]. They found the tensile strength was reduced with increasing of hemp fibers into PLA which was due to the fiber agglomeration creates region of stress concentration that easily gives in under pressure.…”
Section: Resultssupporting
confidence: 84%
“…1 shows the tensile strength continuously decreases with the increasing percentage of RS. Similar result was found by Yakaba et al [8]. They found the tensile strength was reduced with increasing of hemp fibers into PLA which was due to the fiber agglomeration creates region of stress concentration that easily gives in under pressure.…”
Section: Resultssupporting
confidence: 84%
“…The percentage swelling in benzene, toluene and xylene where found to decrease with increased carbonization. [16] studied the physicomechanical effects of surface-modified sorghum stalk powder on reinforced natural rubber, and found that fillers reduces the water absorption resistance which is in agreement with Ragumathen et al, (2011). In this study, Carbonized PalmKernel Shells (CPKS) and Activated Palm Kernel Shells (APKS) were considered as reinforcing fillers in rubber.…”
Section: Introductionsupporting
confidence: 81%
“…Sorghum as a fibre reinforced matrix polymer has been studied with Qi et al, Jing Zhong et al, and M.K. Yakubu, et al [19][20][21][22]. They found that sorghum fibre can be used as a reinforced candidate for thermoplastic composite and bio-composite polymers matrix.…”
Section: Introductionmentioning
confidence: 99%